Presence of occult HBV, but near absence of active HBV and HCV infections in people infected with HIV in rural South Africa - (:unkn) unknown (My University, 2011)
Human immunodeficiency (HIV), hepatitis B (HBV) and hepatitis C (HCV) viruses are endemic in Sub-Saharan Africa, but data regarding the prevalence of hepatitis co-infections in HIV-positive individuals residing there are limited. The aim of the study was to determine the prevalence of HBV, HCV and occult HBV (presence of HBV-DNA in the absence of HBsAg) in a rural, South African cohort. The results were compared to various ethnic groups in a Dutch cohort of people infected with HIV. Antiretroviral-naïve individuals with HIV from both a rural South African clinic (n=258), and a Dutch University hospital (n=782), were included. Both serological (HBV and HCV) and molecular (occult HBV) assays were performed. Logistic regression analysis was used to define independent predictors of a hepatitis co-infection. HBV and HCV prevalence rates in the South African cohort were exceptionally low (0.4%, 1/242 and 0.8%, 2/242 respectively), compared to those observed in Caucasians (HBV 4.4%, HCV 10.9%) and African immigrants (HBV 8.9%, HCV 4.8%). Conversely, occult HBV was observed in a considerable proportion (10%, 6/60) of South African patients who were anti-HBc-positive but HBsAg-negative. Occult infections were less frequent in Caucasians and Africans in the Dutch cohort (3.2% and 1.4% respectively). Independent predictors for occult HBV were not identified, but a trend towards more occult HBV at lower CD4 counts was observed. Local HBV/HCV prevalence data are needed to optimise vaccination and antiretroviral treatment strategies. Occult HBV in patients with HIV may be missed regularly when molecular analyses are not available.
Keywords: African Research